A comparison of two types of sheep grazing management in a forest-grass steppe ecotone in southern Patagonia - Ormaechea, Sebastián Gabriel; Peri, Pablo Luis; Cipriotti, Pablo Ariel; Anchorena, Juan A. (IRC, 2011)
A sustainable silvopastoral production in southern Patagonia ranch is the key for conservatioon of Nothofagus antarctica native forest under grazing management. The goal of this work was to compare the traditional grazing management whith a integral silvopastoral management that included strategic separation in homogenous areas (grass steppe, forest and riparian meadows) and stocking rate adjustment to grassland net primary production in order to increase the production levels of the extensive sheep farms in the forest grass steppe region with a sustainable practice. EEA Santa Cruz Fil: Ormaechea, Sebastián Gabriel. Instituto Nacional de Tecnología Agropecuaria (INTA), Estación Experimental Agropecuaria Santa Cruz; Argentina. Fil: Peri, Pablo Luis. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Fil: Peri, Pablo Luis. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fil: Cipriotti, Pablo Ariel. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Métodos Cuantitativos y Sistemas de Información; Argentina. Fil: Cipriotti, Pablo Ariel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fil: Anchorena, Juan A. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales; Argentina